Pencabutan Permohonan Dalam Praktik Penyelesaian Sengketa Arbitrase - Muhammad Rajha Wardhiyani; Yudi Gunawan; Sawitri Yuli Hartati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the withdrawal of applications in arbitration dispute resolution practices in Indonesia from a normative legal perspective. Arbitration is designed as an efficient, final, and binding mechanism for resolving disputes outside the court system; however, the practice of withdrawing arbitration applications raises legal uncertainty due to the absence of explicit regulatory provisions. Law Number 30 of 1999 on Arbitration and Alternative Dispute Resolution does not comprehensively regulate the procedures, requirements, or legal consequences of such withdrawals. As a result, arbitration institutions apply differing approaches, which may affect procedural consistency and legal certainty. This research employs a normative juridical method by analyzing statutory regulations, arbitration institutional rules, Constitutional Court decisions, and relevant legal doctrines. The findings indicate that the lack of clear legal standards allows potential misuse of withdrawal rights and creates disparities in arbitration practice. In the context of sharia arbitration, this issue also relates to ethical principles and the protection of fairness in muamalah transactions. Therefore, strengthening legal norms and institutional guidelines regarding the withdrawal of arbitration applications is essential to ensure justice, legal certainty, and the credibility of arbitration as an alternative dispute resolution mechanism in Indonesia.